Hubungan Persepsi Pola Asuh Permisif Ayah dan Kecenderungan Perilaku Cyberbullying Remaja Usia 12-18 Tahun - Cyntia Dewi Dewanti; Margaretha Purwanti; Aireen Rhammy Kinara Aisyah (Faculty of Psychology, Atma Jaya Catholic University of Indonesia, 2021)
Cyberbullying among teenagers in Indonesia continues to increase, especially during this Covid-19 pandemic. One of the factors that trigger cyberbullying behavior in adolescents is the application of parenting. Permissive parenting is thought to have a relationship with the occurrence of cyberbullying. In parenting, fathers tend to be less involved even though they have a role that is no less important than mothers. Therefore, this researcher's question is whether the perception of permissive parenting is related to the tendency of cyberbullying behavior in adolescents aged 12-18 years. This research uses a quantitative approach with a correlational design and used a convenience sampling and obtained as many as 123 participants. The characteristics of the participants in this study were male/female aged 12-18 years who had social media and still had a father and still lived together. Results shows that there is a significant relationship between perceptions of permissive parenting and cyberbullying tendencies. The correlation results obtained are r = 0.580, p = < .001. This research concluded that increasing adolescents' perceptions of permissive parenting applied by fathers, the higher the tendency of adolescents to do cyberbullying.